Amygdalar Corticotropin-Releasing Factor Signaling Is Required for Later-Life Behavioral Dysfunction Following Neonatal Pain - Davis, Seth M.; Zuke, Jared T.; Berchulski, Mariah R.; Burman, Michael A. (Frontiers in Physiology, 2021)
Neonatal pain such as that experienced by infants in the neonatal intensive care unit is known to produce later-life dysfunction including heightened pain sensitivity and anxiety, although the mechanisms remain unclear. Both chronic pain and stress in adult organisms are known to influence the CRF system in the Central Nucleus of the Amygdala, making this system a likely candidate for changes following neonatal trauma. To examine this, neonatal rats were subjected to daily pain, non-painful handling, or left undisturbed for the first week of life. Beginning on postnatal day 24 male and female rats were subjected to a 4-day fear conditioning and sensory testing protocol. Some subjects received intra-amygdalar administration of either Vehicle, the CRF1 receptor antagonist Antalarmin, or the CRF2 receptor antagonist Astressin 2B prior to fear conditioning and somatosensory testing, while others had tissue collected following fear conditioning and CRF expression in the CeA and BLA was assessed using fluorescent in situ hybridization. CRF1 antagonism attenuated fear-induced hypersensitivity in neonatal pain and handled rats, while CRF2 antagonism produced a general antinociception. In addition, neonatal pain and handling produced a lateralized sex-dependent decrease in CRF expression, with males showing a diminished number of CRF-expressing cells in the right CeA, and females showing a similar reduction in the number of CRF-expressing cells in the left BLA compared to undisturbed controls. These data show that the amygdalar CRF system is a likely target for alleviating dysfunction produced by early-life trauma, and that this system continues to play a major role in the lasting effects of such trauma into the juvenile stage of development.